1983
DOI: 10.1007/bf00043025
|View full text |Cite
|
Sign up to set email alerts
|

Phytomass structure of natural plant communities on spodosols in southern Venezuela: The tall Amazon Caatinga forest

Abstract: The phytomass structure of the evergreen lowland forest vegetation (Tall Amazon Caatinga) supported by tropaquods near San Carlos de Rio Negro, Federal Amazon Territory of Venezuela was studied in 13 10 m X 10 m plots. The plots were laid out subjectively to cover a low topographical gradient along which the forest on tropaquod is grading into a low woodland (Bana, or Low Amazon Caatinga). The phytomass was estimated by destructive sampling.The total living phytomass (dry matter) varies between I99 t/ha in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 20 publications
3
31
0
3
Order By: Relevance
“…The average dry above-ground phytomass in the Tall Caatinga is 280 t/ha (Klinge & Herrera, 1983). The average root contribution to total phytomass is 34% in the Tall Caatinga.…”
Section: Possible Explanation Of the Transition From Tall Amazon Caatmentioning
confidence: 87%
See 2 more Smart Citations
“…The average dry above-ground phytomass in the Tall Caatinga is 280 t/ha (Klinge & Herrera, 1983). The average root contribution to total phytomass is 34% in the Tall Caatinga.…”
Section: Possible Explanation Of the Transition From Tall Amazon Caatmentioning
confidence: 87%
“…This is reflected by the basal area values. Comparing the Bana values for both basal area and above-ground phytomass to those for Tall Amazon Caatinga (Klinge & Herrera, 1983), it is observed that the basal area in the Bana with relatively low biomass is disproportionately high. This observation provides evidence that towards Open Bana the radial growth of the boles of Bana trees increases progressively relatively to their height growth ( Fig.…”
Section: Zonation Of the Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of data on above-ground litter production exists for various parts of the world (e.g., Bray & Gorham 1964;Bongers etal. 1985;Klinge & Herrera 1983;Meentemeyer etaL 1982;Proctor 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Para determinar y monitorear el almacenamiento de carbono orgánico en sistemas forestales y agroforestales, se debe estimar la diferencia de carbono almacenado en suelos y en la biomasa para sitios con el proyecto y sin este sobre un período de tiempo específico; la diferencia en la cantidad de carbono almacenado es el carbono secuestrado por el proyecto. Existen dos técnicas de monitoreo que pueden ser usadas para evaluar el carbono fijado en proyectos forestales (Araujo, Higuchi & de Carvalho, 1999;Brown, 1999;Brown, Gillespie & Lugo, 1989, Brown & Lugo, 1984Chave et al, 2004;Chave et al, 2014;Cifuentes et al, 2015;Francis, 2000;Jordan & Uhl, 1978;Klinge & Herrera, 1983;Petrokofsky et al, 2012;Saldarriaga, West, Tharp & Uhl, 1988;Schlegel, 2001) y recomendadas por el IPCC (1996): -Modelaje o método indirecto: se calcula la biomasa del árbol con ecuaciones o modelos matemáticos calculados por medio de análisis de regresión entre variables de los árboles, tales como el diámetro a la altura del pecho (dap), la altura comercial (h c ) y total (h t ), el crecimiento diamétrico, el área basal y la densidad específica de la madera. También puede estimarse la biomasa a partir del volumen del fuste, y usar luego la densidad básica de la madera para calcular el peso seco y un factor de expansión para calcular el peso total del árbol.…”
Section: Cuantificación De Biomasaunclassified